(untitled) - Olah, George A. (Hoboken, N.J., 2008)
Superelectrophiles and Their Chemistry contains, for the first-time, a discussion of the basics of this emerging field of organic chemistry, alongside tools to help the reader apply the chemistry. Specific tools include an evaluation of the ways to increase the strength of electrophiles, the classification of superelectrophiles, the solvation issues, a review of methods for studying superelectrophilicity, with details of the superelectrophiles that have been identified and studied. Additional information includes substituent effects in activation of superelectrophiles, and solvation in chemical reactions, as well as an insightful look into future applications.
Keywords: Superelectrophiles,Chemical affinity,Organic compounds,Tác nhân siêu thân điện tử,Ái lực hoá học,Hợp chất hữu cơ; Synthesis,Sự tổng hợp